Molecular screening for microdeletions at 9p22-p24 and 11q23-q24 in a large cohort of patients with trigonocephaly. - Jehee, F; Johnson, D; Alonso, L; Cavalcanti, D; de Sá Moreira, E; Alberto, F; Kok, F; Kim, C; Wall, SA; Jabs, E; Boyadjiev, SA; Wilkie, A; et al. (2005)
Trigonocephaly is a rare form of craniosynostosis characterized by the premature closure of the metopic suture. To contribute to a better understanding of the genetic basis of metopic synostosis and in an attempt to restrict the candidate regions related to metopic suture fusion, we studied 76 unrelated patients with syndromic and non-syndromic trigonocephaly. We found a larger proportion of syndromic cases in our population and the ratio of affected male to female was 1.8 : 1 and 5 : 1 in the non-syndromic and syndromic groups, respectively. A microdeletion screening at 9p22-p24 and 11q23-q24 was carried out for all patients and deletions in seven of them were detected, corresponding to 19.4% of all syndromic cases. Deletions were not found in non-syndromic patients. We suggest that a molecular screening for microdeletions at 9p22-p24 and 11q23-q24 should be offered to all syndromic cases with an apparently normal karyotype because it can potentially elucidate the cause of trigonocephaly in this subset of patients. We also suggest that genes on the X-chromosome play a major role in syndromic trigonocephaly.